Innovation and winemaking by-product valorization: an ohmic heating approach - Coelho, Marta C. (2023)
The by-products of the winemaking process can represent chances for the development of new products. This study focused on the “zero waste” strategy development for by-products generated within winemaking from white and red grape varieties cultivated in the north of Portugal. The phytochemical properties of by-products were identified and characterized. Ohmic heating (OH) as a green extraction method was also applied to grape pomace due to their unknown effects on centesimal and phytochemical compositions. Both protein and carbohydrates were shown to be higher in grape bagasse than in stems. Additionally, red bagasse is richer in bioactive compounds (BC) than white bagasse. The sugar content was 21.91 and 11.01 g/100 g of DW in red and white grape bagasse, respectively. The amount of protein was 12.46 g/100 g of DW for red grape bagasse and 13.18 g/100 g of DW for white. Regarding the extraction methods, two fractions were obtained, a liquid fraction and solid (the remainder after the methodology application). OH presented a higher antioxidant capacity than a conventional (CONV) method. In addition, both extracts presented similar contents of anthocyanins, e.g., delphinidin-3-O-glucoside, petunidin-3-O-glucoside, and peonidin-3-O-glucoside. The solid fraction presented higher amounts of protein and phenols bound to fiber than CONV, which allows its use as a functional ingredient. In conclusion, OH can be an alternative extraction method compared with CONV methods, avoiding non-food grade solvents, thus contributing to circular economy implementation.